Editorial: Gender intentional crop breeding: From integration to institutional innovation - Tufan, H.A.; Polar, Vivian; Ashby, J.A. (2025)
This editorial argues that truly transformative genetic improvement must be gender-intentional, not only by integrating gender analysis but also by reconfiguring institutions, methods, metrics, and incentives. Drawing on experiences across multiple crops and regions, the article argues that the transition to participatory, demand-driven breeding, co-designed with both women and men as users, is key to increasing adoption, equity, and impact. The document aligns strongly with Systems Transformation, Crop Improvement, and Gender Equality, and offers a key strategic framework for the CGIAR and CIP agenda on inclusive breeding.